Brain abscess due to spingomonas paucimobilis infection preceded by non-traumatic intracerebral hemorrhage in the same site - Akbar, Muhammad; Eka, Wiyasih W.; Wuysang, Audry D. (Hasanuddin University, 2023)
AbstractObjective: This case report aims to describe a case of cerebral abscess due to a Spingomonas paucimobilis infection preceded by intracerebral hemorrhage at the same location.Methods: Approach and management of a 48-year-old man with worsening consciousness and fever with a history of intracerebral hemorrhage that occurred eight weeks agoResults:A previous 8-week head CT scan showed a well-defined, oval-shaped, hyperdense lesion in the right frontotemporoparietal region, along with perifocal edema, left lateral ventricular compression, and midline shift to the left of 1.3 cm, with an impression of right temporoparietal lobe intracerebral hemorrhage. A head CT scan at the time of initial admission showed a well-defined, round hypodense lesion with ring enhancement, perifocal edema, left lateral ventricular compression, and a midline shift to the left of 1.4 cm at the same site with previous intracerebral hemorrhage, with the impression of a cerebral abscess. Spingomonas paucimobilis was discovered in the brain matter culture. The diagnosis of cerebral abscess can be established.Conclusion: Cerebral abscess may be preceded by a previous intracerebral hemorrhage. A cerebral abscess can be caused by a Spingomonas paucimobilis infection, especially in immunodeficiency conditions. With additional monitoring, switching from intravenous to oral antibiotic therapy can be considered if there is a clinical and radiographic improvement.